EFEKTIVITAS PENERAPAN YURISPRUDENSI MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 179/K/SIP/1961 DI DALAM PERSAMAAN HAK MEWARIS ANAK LAKI-LAKI DAN ANAK PEREMPUAN PADA MASYARAKAT SUKU BATAK TOBA PERKOTAAN (Studi di Kecamatan Medan Baru) - RYNA LELI NAIBAHO (PREMISE LAW JURNAL, 2015)
Changes in Batak Adat Inheritance Laware marked by the release of the jurisprudence of the Supreme Court of Republic Indonesia No. 179 / K / SIP / 1961 on the equal rights to inherit between sons and daugthers. These changes where the son is the heir, while the daughter is not an heir. Based on the above background, it is important to conduct a study onthe effectiveness of the application of jurisprudence of the Supreme Court of the Republic of Indonesia Number 179 /K/SIP/1961. Keywords: Jurisprudence, Equal Right to Inherit